2022
DOI: 10.3389/fimmu.2022.885229
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Serum Matrix Metalloproteinase-3 in Patients With Primary Biliary Cholangitis

Abstract: Background and AimsMetalloproteinases (MMPs) are involved in many distinct processes in the liver. Matrix metalloproteinase-3 (MMP-3) plays an important role in connective tissue remodeling, degradation of collagen (types II, III, IV, IX, and X), proteoglycans, fibronectin, laminin, and elastin. In addition, MMP-3 can also activate other MMPs such as MMP-1, MMP-7, and MMP-9. Primary biliary cholangitis (PBC) is a cholestatic, autoimmune liver disease, characterized by the progressive destruction of intrahepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In 48h after the therapy, the expression of Mmp3 significantly decreases, similar to Mmp2 (Figure 3). As found earlier, stromelysin 1, encoded by Mmp3, contributes to the degradation of collagens, elastin, laminins, and other extracellular proteins [12]. In addition, stromelysin 1 activates several matrix metalloproteinases: namely interstitial collagenase/ MMP1, matrilysin/ MMP7, and gelatinase B/ MMP9, which are necessary for the degradation of proteins located in the dermal extracellular matrix [13].…”
Section: Ofmentioning
confidence: 69%
“…In 48h after the therapy, the expression of Mmp3 significantly decreases, similar to Mmp2 (Figure 3). As found earlier, stromelysin 1, encoded by Mmp3, contributes to the degradation of collagens, elastin, laminins, and other extracellular proteins [12]. In addition, stromelysin 1 activates several matrix metalloproteinases: namely interstitial collagenase/ MMP1, matrilysin/ MMP7, and gelatinase B/ MMP9, which are necessary for the degradation of proteins located in the dermal extracellular matrix [13].…”
Section: Ofmentioning
confidence: 69%
“…Forty-eight hours after the therapy, the expression of Mmp3 significantly decreases, similar to Mmp2 ( Figure 3 ). As found earlier, stromelysin 1, encoded by Mmp3 , contributes to the degradation of collagens, elastin, laminins, and other proteins of the ECM [ 28 ]. Furthermore, stromelysin 1 activates several matrix metalloproteinases: interstitial collagenase/MMP1, matrilysin/MMP7, and gelatinase B/MMP9.…”
Section: Discussionmentioning
confidence: 91%
“…In an early study, proline hydroxylase was elevated in ten out of fourteen patients with PBC but to a lesser degree than in patients with active cirrhosis [ 62 ]. Approximately 60% of PBC patients had increased MMP-3 in serum measured by ELISA, and higher values were found in patients with advanced disease (Ludwig stage III-IV) [ 63 ]. A different research approach showed results consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%